PEMANFAATAN FENOMENA SURFACE PLASMON RESONANCE (SPR) DENGAN MENGGUNAKAN NANOPARTIKEL MAGNETIK Fe3O4 UNTUK DETEKSI BIOMOLEKUL - , SADANG HUSAIN, Prof. Dr. Kamsul Abraha ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The SPR phenomenon has been observed in the biomolecule detection coated by magnetic nanoparticles Fe3O4. The magnetic nanoparticles Fe3O4 mixed with PEG 4000 is used for biomolecule detection optimation. This research uses the attenuated total reflection (ATR) in the Krestchmann configuration with He- Ne laser beam of wavelength 633 nm. The SPR angle for prism/Ag layer system is 43,200Â±0,050 with a constant surface plasmon (SP) wavevector being 1,029ï´107 m-1. For the system due to the addition of the mixed layer of Fe3O4 magnetic nanoparticles, the SPR angle shifts to 43,400Â± 0,05o and a constant SP wavevector is 1,033ï´107 m-1. After reacted with Î±-amylase biomolecule, the SPR angle shifts to 44,300 Â± 0,050 while the constant SP wavevector changes to 1,050ï´107 m-1.